ISLAMIC EDUCATION LEADERSHIP: STUDY ON MADRASAH MANAGEMENT IN INDONESIA (Indonesian Journal of Education (INJOE), 2025)
Islamic Education Management offers about the important study of Madrasah's leadership in Indonesia related to the application of Islamic education principles in managerial practice. Through the analysis of a holistic leadership role that covers professional, ethical, and spiritual aspects applied in Madrasah so that Islamic values can reflect and influence educational management strategies. The research method used is the study of literature by looking for literature in accordance with the context of the research discussed. The results show that the dynamics of Islamic education leadership, including the interaction between traditional and modern values, the application of democratic strategies in decision-making, as well as the implications of these practices for the formation of institutional identities and integrative learning experiences. The research also contributes to the education management literature by identifying key factors that can improve the effectiveness of Madrasah's leadership and suggest practical implications for the development of education policy.